ANALISIS EFEKTIFITAS PEMBELAJARAN MATEMATIKA MELALUI MEDIA GOOGLE CLASSROOM DITINJAU DARI HASIL BELAJAR MAHASISWA (MASA PANDEMIK COVID 19) - Radiatul Adawiah (STKIP Paris Barantai, 2021)
The Google Classroom application is one of the alternative media that can be used in distance learning during the current Covid 19 pandemic. This study aims to analyze the difficulties faced by mathematics education students at STKIP Paris Barantai in online Algebra courses. This type of research is a qualitative descriptive study. The subjects of this study were students programming algebra courses. The research subjects were selected based on the snowball sampling technique. added a questionnaire about student difficulties before the protocol analysis was carried out to make it easier to understand the context of the interview and then analyzed the results, it was obtained in general (1) related to the technical difficulties of internet networks and quota that many students complained about, (2) difficulties in using the Google Classroom Application in principle can be used, it just needs to add applications that make it easier to communicate virtually. (3) related to the unpreparedness of the lecturer. Material delivery was not diverse and only relied on PPT or PDF